World of work report 2010 : from one crisis to the next? (ILO, 2010)
Published annually by the International Institute for Labour Studies - the research arm of the ILO - the 2010 edition of "World of Work Report" assesses the state of labour markets worldwide amid the economic crisis and analyses the economic and social implications.